As contribuições do NEABI (Núcleo de Estudos Afro-Brasileiros e Indígenas) para o aquilombamento bibliográfico nas bibliotecas do Instituto Federal de São Paulo: reflexões preliminares - Salles, Tatiane Helena Borges de (2025)
The objective of this research was to examine the relevance of an aquilomamed collection in the struggle against epistemic, social and racial injustices that affect the black population, which faces the erasure and systematic silencing of their voices and knowledge from orality. The study focuses on the successful experience of Neabi (Center for Afro-Brazilian and Indigenous Studies) of the Federal Institute of Education, Science and Technology of São Paulo (IFSP) in their collaboration with libraries, in order to promote specific training for librarians, highlighting the importance of laws 10.639/2003 and 11.645/2008, which deal with education for ethnic-racial relations. Specific objectives include describing Neabi's actions in partnership with libraries; highlight the initiatives of libraries IFSP in the promotion of cultural activities and extension projects as ways to encourage reading and informational literacy Afro -centered; and analyze the titles of black authors available in the IFSP collection. To achieve project goals, we use a methodology that combines exploratory and bibliographic research, followed by an empirical procedure to evaluate projects qualitative centered on Afrocentricity. Thus, the data collected comes from empirical and bibliographic studies that develop actions related to ethnic-racial theme in libraries. The results reveal the importance of including Afro -centered works in the collections to promote the informational and racial literacy of users, the relevance of Aquilomation in the Collections for Construction of a new narrative based on Afrocentricity and the opposition to the coloniality that students bring to the academic environment. In addition, they demonstrate how the activities performed in libraries, through cultural actions, extension projects and research, may favor anti -racist education in these spaces.